Comparative analysis of stress levels and coping strategies in parents of neurodivergent and neurotypical children - Lessa A. Méndez-Lara; Rodrigo Ramirez-Rodriguez; Edgar Santos; Angel Puig-Lagunes (Frontiers in Child and Adolescent Psychiatry)
Parents of children with autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD) face unique challenges that may significantly increase stress levels, potentially impacting the emotional well-being of the entire family. In Mexico, limited research has examined the association between parental stress and coping strategies among families with children with developmental disabilities. This study aimed to compare stress levels and coping strategies among parents of children with ASD, ADHD, and neurotypical developing (NTD) children, as well as to analyze differences in coping styles across these groups. A cross-sectional, descriptive-comparative design was employed with 212 parents of children aged 3 to 5 years, with a formal clinical diagnosis made by a pediatric neurologist. Participants completed validated questionnaires assessing parental stress and coping styles. Results revealed that parents of children with ASD and ADHD reported significantly higher stress levels (M = 116.7 and M = 88.1, respectively) compared to parents of NTD children (M = 67.2). Significant differences in coping strategies were observed (p < .001); 100% of ASD/ADHD parents used emotion-focused coping, whereas 94.93% of NTD parents used problem-focused coping. These findings emphasize the importance of designing interventions to support coping and stress regulation in parents of children with developmental disorders.